A Survey of the Knowledge of and Testing Rate for Hepatitis C in the General Population in South Korea - Choi, Gwang Hyeon (Gut Liver, 2020)
BACKGROUND/AIMS: To eliminate hepatitis C virus (HCV) infection, improving public knowledge of and access to HCV screening and treatment is essential. The aim of this study was to evaluate the knowledge of and testing rate for HCV and the opinions about the inclusion of the HCV test in the National Health Examination (NHE) among the general population in South Korea. METHODS: A telephone interview survey was conducted by an independent research company using a 16 item-questionnaire (demographics, knowledge of HCV, testing and results, need for screening) in May 2019. The sample population consisted of 1,003 adult Korean residents adjusted by age, sex, and area according to the standard Korean population in 2019. RESULTS: Among the 1,003 participants (505 women, mean age of 47.9 years), 56.4% recognized HCV; 44.4% understood that HCV is transmittable, and 56.8% thought that HCV is curable by medication. The recognition rate tended to increase with an increasing level of education. Testing for anti-HCV antibodies was reported by 91 people (9.1%); among them, 10 people (11.0%) reported a positive result, and eight people received treatment. The common reasons for HCV testing were a health check-up (58.5%), a physician’s recommendation (11.0%) and elevated liver enzyme levels (10.7%). The majority of the population (75.1%) agreed with the integration of HCV into the NHE. CONCLUSIONS: The level of knowledge of HCV is suboptimal, and the self-reported testing rate for HCV is less than 10%; however, once HCV infection is diagnosed, the treatment rate seems to be high in South Korea. More active campaigns and effective screening are needed.